Comparison of the effects of some wound healing materials on full thickness skin wounds in rabbits - Kiliç, S; Timurkaan, N; Ünsaldi, S; Günay, C; Istek, O; Yilmaz, B (Tubitak Scientific & Technological Research Council Turkey, 2002)
The values of some materials with various mechanisms of actions on the wound healing were determined using qualitative and quantitative parameters and histopathologic findings. A, total of 48 full thickness skin wounds, 4 from each of 12 rabbits, were created on their dorsal aspects. Of these wounds, 4 were allocated to group 1 (control), 24 to group 2 and 20 to group 3. Op-site, epigard, tagaderm, sclera, rabbit amnion and cow amnion were used in group 2 and yeast, methycellulose (MS), polyethhylenglcacol (PEG), lanolin and silvadene in group 3. Postoperatively, the wound surfaces were macroscopically examined and the effects of different shapes and sites of wounds on the healing process and the rates of wound expansion, contraction and epithelialization processes were quantitatively analyzed. In all groups, epithelialization was first observed (25%) on postoperative day (POD) 4 and covered all wound sites (100%) on POD 16. Wound sites underwent a 25% expansion overall and the rate was higher in group 2 than in groups 1 and 3. The contraction process started on POD 4 and continued until POD 13. With respect to the contraction rate, while the difference between groups was non-significant on POD 7, it was determined to be significant on PODS 10 and 13: As a result, occlusive materials. especially amniotic membranes (group 2) used in this study were seen in general to have a better wound healing feature than non-occlusive ones (group 3).
Keywords: rabbit; wound; healing process; healing materials